Association of hospital nursing and postsurgical sepsis - Dierkes, Andrew M.; Aiken, Linda H.; Sloane, Douglas M.; McHugh, Matthew D. (PloS one, 2021)
Despite concerted research and clinical efforts, sepsis remains a common, costly, and often fatal occurrence. Little evidence exists for the relationship between institutional nursing resources and the incidence and outcomes of sepsis after surgery. The objective of this study was to examine whether hospital nursing resource quality is associated with postsurgical sepsis incidence and survival. This cross-sectional, secondary data analysis used registered nurses’ reports on hospital nursing resources—staffing, education, and work environment—and multivariate logistic regressions to model their association with risk-adjusted postsurgical sepsis and mortality in 568 hospitals across four states. Better work environment quality was associated with lower odds of sepsis. While the likelihood of death among septic patients was nearly seven times that of non-septic patients, better nursing resources were associated with reduced mortality for all patients. Whereas the preponderance of sepsis research has focused on clinical interventions to prevent and treat sepsis, this study describes organizational characteristics hospital administrators may modify through organizational change targeting nurse staffing, education, and work environments to improve patient outcomes.